2023
DOI: 10.3847/1538-4357/acf46a
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength Observations of a B-class Flare Using XSM, AIA, and XRT

Yamini K. Rao,
B. Mondal,
Giulio Del Zanna
et al.

Abstract: We present multiwavelength observations by Chandrayaan-2/Solar X-ray Monitor, Solar Dynamics Observatory/Atmospheric Imaging Assembly, and Hinode/X-Ray Telescope (XRT) of a B-class flare observed on 2021 February 25, originating from an active region (AR 12804) near the northwest limb. The microflare lasts for ∼30 minutes and is composed of hot loops reaching temperatures of 10 MK. We report excellent agreement (within 20%) for the average effective temperatures obtained at the flare peak from all the three in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These abundances are used to calculate the bolometric radiative loss rate that directly impacts the cooling of the plasma. Many recent X-ray observations of flares, however, clearly show that elemental abundances are not fixed and vary with time over the duration of the flare (Del Zanna et al 2021;Mondal et al 2021;Mithun et al 2022;Kepa et al 2023;Nama et al 2023;Rao et al 2023;Suarez & Moore 2023;Woods et al 2023). Similar observations have also found that the abundances of active regions (ARs) vary relatively quickly as well (Mondal et al 2023).…”
Section: Introductionmentioning
confidence: 91%
“…These abundances are used to calculate the bolometric radiative loss rate that directly impacts the cooling of the plasma. Many recent X-ray observations of flares, however, clearly show that elemental abundances are not fixed and vary with time over the duration of the flare (Del Zanna et al 2021;Mondal et al 2021;Mithun et al 2022;Kepa et al 2023;Nama et al 2023;Rao et al 2023;Suarez & Moore 2023;Woods et al 2023). Similar observations have also found that the abundances of active regions (ARs) vary relatively quickly as well (Mondal et al 2023).…”
Section: Introductionmentioning
confidence: 91%
“…A change from coronal-to photospheric-like elemental abundances has sometimes been observed in flares, including microflares of similar brightness to these events (e.g., Rao et al 2023). In addition to the Bremsstrahlung continuum, NuSTAR has sensitivity to spectral lines from elements with low first ionization potential, which are comparatively less abundant in the photosphere.…”
Section: Variable-temperature-range Demsmentioning
confidence: 99%